2009
DOI: 10.1097/rlu.0b013e3181a34525
|View full text |Cite
|
Sign up to set email alerts
|

Integrated PET/CT in Evaluating Sarcomatous Transformation in Osteochondromas

Abstract: Whole body FDG PET-CT is an important adjunct to conventional morphologic imaging in evaluating suspected malignant transformation in osteochondromas. Increased glucose metabolism can help diagnose sarcomatous transformation at the suspected sites as well as detect early malignant change at clinically unsuspected sites. Moreover, its ability to detect a focus of dedifferentiation can be useful for prognostication and to plan adjuvant treatment. A small cohort limits statistically sound conclusions to be drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Studies on the use of PET – CT in the study of sarcomas began to appear after 2001 (Al-Ibraheem et al 2013; Aoki et al 2001, 2003; Benz et al 2009, 2010; Brenner et al 2004; Eary et al 1998, 2002; Feldman et al 2005; Folpe et al 2000; Garcia et al 1996; Purandare et al 2009; Schulte et al 1999). Some authors suggested that because PET – CT detects hyper metabolic foci, that whole body PET – CT could be an important test for identifying chondrosarcomas and their recurrence after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of PET – CT in the study of sarcomas began to appear after 2001 (Al-Ibraheem et al 2013; Aoki et al 2001, 2003; Benz et al 2009, 2010; Brenner et al 2004; Eary et al 1998, 2002; Feldman et al 2005; Folpe et al 2000; Garcia et al 1996; Purandare et al 2009; Schulte et al 1999). Some authors suggested that because PET – CT detects hyper metabolic foci, that whole body PET – CT could be an important test for identifying chondrosarcomas and their recurrence after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There are recent studies advocating PET/CT imaging to monitor known benign exostosis for malignant transformation. (10) Due to the relative rarity of these lesions it is important to review the images and histology in a specialised bone tumour multi-disciplinary meeting.…”
Section: Discussionmentioning
confidence: 99%
“…23 A small study of 12 patients attempted to differentiate the chondrosarcoma subtypes according to their SUVmax. 24 The authors reported SUVmax 0.8e1.3 for benign cartilage tumours, 3.3e6.9 for grade 2 tumours and one patient with de-differentiated chondrosarcoma had SUV of 11.4. Because of the small numbers, it is impossible to apply these numbers generally to chondrosarcoma, but it certainly merits further study.…”
Section: The Role Of Imaging Pet-ctmentioning
confidence: 97%